AN AYURVEDIC AND CONTEMPORARY OVERVIEW OF MENOPAUSE: A CONCEPTUAL APPROACH - Mishra, *Amrita; Shelare, Rajashree Vitthal (International Journal of Ayurveda and Pharma Research, 2018)
Menopause is generally defined as the cessation of menses for period of 12 months or a period equivalent to three previous cycles or the time of cessation of ovarian function resulting in permanent amenorrhea. During the period of menopause the women enters an estrogen deficient phase which leads to the various symptoms. This period is generally associated with manifestation of aging process in women. Other symptoms include hot flushes, sweating, mood changes, loss of libido etc. These symptoms affect the quality of life of the female.Hormone Replacement Therapy (HRT) is the only alternative available for menopausal syndrome in modern medicine. It also has a wide range of side effects on the body of the female.In Ayurveda the context of menopause is depicted as â€œJarapakwa avasthaâ€ of body and Rajonivrutti. Rajonivrutti janya laksana is a group of symptoms produced by degenerative changes in the body. Degenerative changes are explained in Ayurveda as Dhatukshaya lakshana. Vata dosha dominance is seen in the later stage of life. To combat the degenerative process of the body tissue, Acharyas have described Rasayana Chikitsa. Rasayana includes drugs which promotes longevity and improve the quality of life. Thus an effort is being made here, to study the effect of Rasayana therapy, on Menopausal syndrome, conceptually, based on Available information in Ayurvedic texts and other contemporary resources. The basic Rationale for this study is to establish a reliable platform for further Research on the Said subject.